Preoperative Planning Using 3D Reconstructions and Virtual Endoscopy for Location of the Frontal Sinus - Martins, Marcos Jullian Barreto; Aguiar, Carolina Veras; Nogueira, João Flávio, Júnior; Abreu, João Paulo Saraiva; Feijão, Moisés Ximenes; Jataí, Isabelle Oliveira; Bastos, Arthur Chaves Gomes (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: Computed tomography (TC) generated tridimensional (3D) reconstructions allow the observation of cavities and anatomic structures of our body with detail. In our specialty there have been attempts to carry out virtual endoscopies and laryngoscopies. However, such application has been practically abandoned due to its complexity and need for computers with high power of graphic processing.Objective: To demonstrate the production of 3D reconstructions from CTs of patients in personal computers, with a free specific program and compare them to the surgery actual endoscopic images.Method: Prospective study in which the CTs proper files of 10 patients were reconstructed with the program Intage Realia, version 2009, 0, 0, 702 (KGT Inc., Japan). The reconstructions were carried out before the surgeries and a virtual endoscopy was made to assess the recess and frontal sinus region. After this study, the surgery was digitally performed and stored. The actual endoscopic images of the recess and frontal sinus region were compared to the virtual images.Results: The 3D reconstruction and virtual endoscopy were made in 10 patients submitted to the surgery. The virtual images had a large resemblance with the actual surgical images.Conclusion: With relatively simple tools and personal computer, we demonstrated the possibility to generate 3D reconstructions and virtual endoscopies. The preoperative knowledge of the frontal sinus natural draining path location may generate benefits during the performance of surgeries. However, more studies must be developed for the evaluation of the real roles of such 3D reconstructions and virtual endoscopies.
Keywords: computer assisted surgery; video-assisted surgery; tomography; tridimensional image; endoscopy